Laboratory Evaluation of Neem formulation bioactivity against Crocidolomia pavonana F. larvae - Raden Arif Malik Ramadhan; Neneng Sri Widayani; Lindung Tri Puspasari; Yusup Hidayat; Danar Dono (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2018)
This study aims to evaluate the bioactivity of the formulation of Neem 50 EC against Crocidolomia pavonana larvae in the laboratory. The study using six treatments and three replications. The treatment consisted of the formulation of neem 50 EC at concentrations of 0.3%, 0.5%, 0.8%, 1.3%, 2.3%, and control. The treatment was done by leaf feeding method and tested on C. pavonana instar II. The results of the research showed that the formulation of neem 50 EC at concentration of 2.3% caused mortality of C. pavonana larvae with mortality rate of 95% and has LC50 value aqual to 0.83%. Neem formulation can inhibit the development of C. pavonana larvae from instar I to instar IV, decrease food consumption, and decrease the dry weight of C. pavonana larvae instar IV.Keywords: Azadirachta indica, Bioactivity, Crocidolomia pavonana, neem formulation